Analisis Normatif Hukum Jaminan (Rahn) dalam Fiqh Muamalah : Studi Komparasi dengan Undang-Undang Perbankan Syariah di Indonesia - Dian Syaharania; Ahmad Liano Al-Fayed; Fatih Fabrian Ariawisesa; Holijah Holijah (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study normatively analyzes the law of rahn guarantee in Islamic jurisprudence and compares it with the provisions of the Sharia Banking Law (Law No. 21 of 2008) in Indonesia. The background of the problem arises from differences in the interpretation of rahn as a sharia fiduciary guarantee contract that often clashes with conventional banking practices, thus creating legal uncertainty in Islamic financial transactions. The purpose of the study is to identify the normative conformity between the principles of Islamic jurisprudenc such as ownership of pledge rights, prohibition of usury, and gharar with Islamic banking regulations, and to provide recommendations for harmonization. A normative juridical approach with an analytical comparative method is used, analyzing primary sources such as the Qur'an, Hadith, fiqh books (Al-Muwatta' and Al-Mughni), as well as the Sharia Banking Law and fatwas of the DSN-MUI. The findings indicate that rahn in Islamic jurisprudence emphasizes absolute ownership for the mortgagor with full redemption rights, while the Sharia Banking Law tends to adopt a fiduciary model with conventional elements such as the right to deposit collateral with the bank. This difference has the potential to give rise to hidden usury practices. Regulatory revisions are recommended to strengthen pure Sharia principles to support Islamic financial inclusion in Indonesia.